2005
DOI: 10.1243/146808705x7374
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of lubrication in a journal bearing by a thermoelastohydrodynamic lubrication (TEHL) model

Abstract: In recent years, in high power, compact, and light weight automotive engines, the bearing load has been increasing and the housing stiffness has been decreasing. The engine bearing performance is significantly influenced by both an elastic deformation and an increase in temperature. Under these harsh operating conditions, an extreme temperature rise of the bearing is expected to occur in the thin oil-film region when the oil-film thickness is not kept thick enough within the bearing. Consequently, the high-tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In addition, the fully flooded condition is assumed in the current study. The research on the deformation and starved lubrication can be found in Okamoto, 38 Liu et al, 39 Li et al, 40 Syed and Wani. 41…”
Section: Mathematical Modelmentioning
confidence: 99%
“…In addition, the fully flooded condition is assumed in the current study. The research on the deformation and starved lubrication can be found in Okamoto, 38 Liu et al, 39 Li et al, 40 Syed and Wani. 41…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Proportional damping is applied on the structure, a damping matrix is proposed as pp   B M K (9) Matrix of the relative velocity of elastic deformation E H is obtained by Newmark's algorithm using previous time step values as…”
Section: Structural Region Descriptionmentioning
confidence: 99%
“…Brief overview of an elasto-hydrodynamic solution presents, e.g. Thomas [6], Caika [7], Javorova [8] or Okamoto [9]. The publishing of exclusively general procedures is the main disadvantage of similar technical contributions, while detailed instructions for the numerical solution is not presented often.…”
Section: Introductionmentioning
confidence: 99%